Weaning management in a patient with heart dysfunction: a case report - Jiang, Haobo; Lao, Meiling; Xu, Weixian; Zhang, Yunhai (Frontiers in Physiology, 2025)
BackgroundPatients undergoing weaning from mechanical ventilation face the risks of reintubation. Spontaneous breathing trials (SBTs), including T-piece (SBT-T) and pressure support (SBT-P), are commonly used to assess extubation readiness. Current guidelines favor the use of SBT-P. Weaning-induced pulmonary edema (WIPO) is common after extubation, which could lead to extubation failure.CaseWe report the case of a patient on ventilation who failed the first extubation attempt following successful SBT-P due to WIPO. SBT-T was implemented for the patient in the second weaning attempt.MethodsDuring the subsequent SBT-T, signs of WIPO recurred. Instead of terminating the trial, we managed the patient with intensive monitoring, fluid management, and blood pressure control.ResultAfter targeted interventions, this patient was successfully extubated during the second weaning attempt.ConclusionThis case highlights the utility of SBT-T in unmasking WIPO risk in weaning patients with cardiac dysfunction. By enabling proactive management during the trial, SBT-T may enhance safety in high-risk populations.